2017
DOI: 10.1021/acs.jafc.7b01804
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of a Leonardite Iron Humate Improving Fe Nutrition As Revealed in Silico, in Vivo, and in Field Experiments

Abstract: Novel, cheap and ecofriendly fertilizers that solve the usual iron deficiency problem in calcareous soil are needed. The aim of this work is to study the long-term effect of an iron leonardite fertilizer on citrus nutrition taking into account a properly characterization, kinetic response with a ligand competition experiment, efficiency assessment using Saccharomyces cerevisiae strain and finally, in field conditions with citrus as test plants. Its efficiency was compared with the synthetic iron chelate FeEDDH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 30 publications
5
25
0
Order By: Relevance
“…The products S and M, prepared from 57 Fe 2 (SO 4 ) 3 , at their second dose (75 μmol 57 Fe pot -1 ) and the product F, prepared from 57 Fe(NO 3 ) 3 at the third dose (150 μmol 57 Fe pot -1 ) showed the highest Fe Fer increase between sampling times. These results are consistent with our previous data (Cieschi et al, 2017) on fertilization with iron leonardite humate which sustained slow and increasing iron nutrition to citrus growth under conditions of calcareous soil and yielded results similar to FeEDDHA with regard to efficacy of iron deficiency correction during the first year of application.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The products S and M, prepared from 57 Fe 2 (SO 4 ) 3 , at their second dose (75 μmol 57 Fe pot -1 ) and the product F, prepared from 57 Fe(NO 3 ) 3 at the third dose (150 μmol 57 Fe pot -1 ) showed the highest Fe Fer increase between sampling times. These results are consistent with our previous data (Cieschi et al, 2017) on fertilization with iron leonardite humate which sustained slow and increasing iron nutrition to citrus growth under conditions of calcareous soil and yielded results similar to FeEDDHA with regard to efficacy of iron deficiency correction during the first year of application.…”
Section: Resultssupporting
confidence: 92%
“…Most agricultural soils contain natural ferrihydrite NPs, which may contribute to iron nutrition of plants. Many authors (Römheld and Nikolic, 2007; Colombo et al, 2012; Cieschi et al, 2017) reported ferrihydrite formation during the iron humate synthesis, they characterized and studied the relationship between the particle size, pH and stability. Angelico et al (2014) and Colombo et al (2015) have shown that the phase of iron (hydr)oxide formed in the presence of HS depends on pH, oxidation rate, and Fe:HS ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main component denoted by Fe 3+ A with δ = 0.37 mm s −1 , Δ = 0.75 mm s −1 and a = 56% represents a high‐spin Fe 3+ that can be associated with ferrihydrite. The Fe 3+ B has δ = 0.38 mm s −1 , Δ = 1.22 mm s −1 and a = 44% compatible with Fe 3+ polynuclear structures . Attending to Fe 2+ :G7 (1:2) spectrum (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Recently, it has been demonstrated that Fe complexed by HA extracted from Leonardite can serve as Fe source for plants (Colombo et al, 2012). Indeed, HA extracted from Leonardite can positively influence plants' metabolism (Cieschi et al, 2017), while Fe-HA complexes can reach the plasma membrane of root cells and then enter the cell (Kulikova et al, 2017). This observation was ascribed to the root capability of mobilizing Fe directly from ferrihydrite particles trapped in the niches of the poorly ordered crystalline Fe-Leonardite coprecipitates (Ková cs et al, 2013).…”
Section: Introductionmentioning
confidence: 99%